URGENCY OF INSURANCE AGENT'S LEGAL RELATIONSHIP WITH INSURANCE COMPANY - Suarthini, Ni Made; Priyanto, I Made Dedy (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2022)
This research aims to discover about and comprehend the legal framework that underpins the partnership between insurance agents and insurance companies. The research method used is a type of normative legal research. The type of approach used is a statutory approach and a conceptual approach. The laws used are the Civil Code, the Commercial Code, the Insurance Law and POJK.05/2013 concerning Insurance Products and Insurance Marketing. The results of this study revealed that the legal basis for the relationship between insurance agents and insurance companies is not expressly regulated in the Civil Code, Commercial Code, Insurance Law and Financial Services Authority (OJK) Regulations. The Insurance Law only provides a definition of insurance agents and insurance companies. As such, the legal relationship between insurance agents and insurance companies is not regulated. As a legal basis, the relationship between the insurance agent and the insurance company lies in the agreement made by the agent with the company. Thus, the agreement becomes the legal basis for the relationship between the insurance agent and the insurance company. Meanwhile, the legal relationship between an insurance agent and an insurance company is a contractual relationship or a relationship that is bound in an agreement.